CTNNAL1 inhibits ozone‐induced epithelial–mesenchymal transition in human bronchial epithelial cells. Issue 8 (6th July 2018) - Tan, Meiling; Liu, Caixia; Huang, Wenjie; Deng, Linhong; Qin, Xiaoqun; Xiang, Yang
Abstract : New Findings: What is the central question of this study? What is the effect of catenin alpha‐like 1 ( CTNNAL1 ), an asthma‐related epithelial adhesion molecule that plays a vital role in airway epithelial wound repair, on airway epithelial–mesenchymal transition? What is the main finding and its importance? CTNNAL1 inhibits ozone‐induced airway epithelial–mesenchymal transition features, mediated by repressing the expression of Twist1 mRNA and reducing TGF‐β1 levels. These findings contribute to our understanding of the pathology of airway EMT and may indicate a possible therapeutic target for airway remodelling in bronchial asthma. Abstract: Epithelial–mesenchymal transition (EMT), a crucial event occurring during epithelial and mesenchymal repair, was reported to be a possible mechanism for airway remodelling. Our previous work showed that the expression of catenin alpha‐like 1 ( CTNNAL1 ) was down‐regulated in the bronchial epithelial cells of asthmatic models and played a vital role in airway epithelial wound repair. The aim of this study was to investigate the effect of CTNNAL1 on airway EMT. Overexpression or silencing of CTNNAL1 in human bronchial epithelial cells was induced by stable transfection. CTNNAL1 was silenced in primary mouse airway epithelial cells with an effective siRNA vector. Cells were stressed by ozone for 4 days at 30 min day −1 to induce EMT. EMT features, changes in the function of co‐cultured lung fibroblasts, changes in the expression of the transcriptional repressors Snail / Slug and Twist1 / Twist2 and changes in the secretion of transforming growth factor β1 (TGF‐β1) were assayed in different cell lines with or without ozone exposure. Both ozone exposure and silencing of CTNNAL1 induced EMT features in airway epithelial cells. Functional changes in lung fibroblasts increased after co‐culture with (ozone‐stressed) CTNNAL1 ‐silenced cells. Snail and Twist1 expression increased, and the level of TGF‐β1 was enhanced. Conversely, CTNNAL1 overexpression reversed EMT features, repressed mRNA levels of Twist1 and reduced the secretion of TGF‐β1, both alone and in combination with ozone exposure. Our results indicate that ozone exposure induces airway EMT and that CTNNAL1 inhibits ozone‐induced airway EMT. CTNNAL1 may play a role in airway EMT by repressing the expression of Twist1 mRNA and reducing the level of TGF‐β1. Abstract :